Morbidity profile of elderly individuals in urban Visakhapatnam - Polisetty, Sanjay; Seepana, Madhavi (International Journal Of Community Medicine And Public Health, 2017)
Background: India has acquired the label of “an ageing nation” with 7.7% of its population being more than 60 years old. Both perceived health and chronic illness are major elements of health status in elderly and there is growing evidence that older people are at risk for manifold co-morbidities. Methods: A community based cross sectional study was conducted in the Allipuram urban-Field practice area, Visakhapatnam for a period of 2 months (May 1st to June 30th) using a pretested questionnaire in the native language. Study subjects were individuals above 60 years of age who are willing to participate. Data collected for this study was predominantly based on the symptoms experienced by the individuals and patient records. Results: Almost the entire study population (99.6%) suffered from either some form of acute or chronic morbidity. More than 70% of individuals had eye problems, most common problem being cataract (60%). Hypertension was present in 49% of individuals (24.3% Males and 24.7% Females). About 74.2% of Diabetics were also hypertensives and the relation was found to be highly significant (p<0.05). Conclusions: Old age is associated with increasing morbidity due to senile changes, lowered immunity and increased susceptibility to most diseases hence it is of paramount importance that efficient and appropriate means of health care delivery to the geriatric population is ensured.